Population variation and natural selection on leaf traits in cork oak throughout its distribution range - Ramírez-Valiente, José Alberto; Valladares, Fernando; Sánchez-Gómez, David; Delgado, Antonio; Aranda, Ismael (Acta Oecologica, 2014)
A central issue in evolutionary biology is the exploration of functional trait variation among populations and the extent to which this variation has adaptive value. It was recently proposed that specific leaf area (SLA), leaf nitrogen concentration per mass (Nmass) and water use efficiency in cork oak play an important role in adaptation to water availability in the environment. In order to investigate this hypothesis, we explored, first, whether there was population-level variation in cork oak (Quercus suber) for these functional traits throughout its distribution range; if this were the case, it would be consistent with the hypothesis that different rainfall patterns have led to ecotypic differentiation in this species. Second, we studied whether the population-level variation matched short-term selection on these traits under different water availability conditions using two fitness components: survival and growth. We found high population-level differentiation in SLA and Nmass, with populations from dry places exhibiting the lowest values for SLA and Nmass. Likewise, reduced SLA had fitness benefits in terms of growth for plants under dry conditions. However, contrary to our expectations, we did not find any pattern of association between functional traits and survival in nine-year-old saplings despite considerable drought during one year of the study period. These results together with findings from the literature suggest that early stages of development are the most critical period for this species. Most importantly, these findings suggest that cork oak saplings have a considerable potential to cope with dry conditions. This capacity to withstand aridity has important implications for conservation of cork oak woodlands under the ongoing climate change.
Keywords: Adaptation; Nitrogen leaf content; Phenotypic selection; Population divergence; Specific leaf area; water use efficiency

Relationships between leaf morphological traits, nutrient concentrations and isotopic signatures for Mediterranean woody plant species and communities - Domínguez, María T.; Aponte, Cristina; Pérez-Ramos, Ignacio M.; García, Luis V.; Villar, Rafael; Marañón, Teodoro (Plant and Soil, 2012)
Background and aims Soil factors are driving forces that influence spatial distribution and functional traits of plant species. We test whether two anchor morphological traits—leaf mass per area (LMA) and leaf dry matter content (LDMC)—are significantly related to a broad range of leaf nutrient concentrations in Mediterranean woody plant species. We also explore the main environmental filters (light availability, soil moisture and soil nutrients) that determine the patterns of these functional traits in a forest stand. Methods Four morphological and 19 chemical leaf traits (macronutrients and trace elements and δ 13 C and δ 15 N signatures) were analysed in 17 woody plant species. Community-weighted leaf traits were calculated for 57 plots within the forest. Links between LMA, LDMC and other leaf traits were analysed at the species and the community level using standardised major axis (SMA) regressions Results LMA and LDMC were significantly related to many leaf nutrient concentrations, but only when using abundance-weighted values at community level. Among-traits links were much weaker for the crossspecies analysis. Nitrogen isotopic signatures were useful to understand different resource-use strategies. Community-weighted LMA and LDMC were negatively related to light availability, contrary to what was expected. Conclusion Community leaf traits have parallel shifts along the environmental factors that determine the community assembly, even though they are weakly related across individual taxa. Light availability is the main environmental factor determining this convergence of the community leaf traits.
Keywords: Community weighted means; functional traits; isotopes; leaf dry matter content; Leaf mass per area; macronutrients; Specific leaf area

Intraspecific competition and water use efficiency in Quercus suber: evidence of an optimum tree density? - Gouveia, António C; Freitas, Helena (Trees, 2008)
The dehesa and montado agroecosystems seem to be water-stress induced structures and some authors have found evidence of a relationship between stand tree density and mean annual precipitation. In order to assess the ecophysiological responses of Quercus suber to increasing tree density and to evaluate if there was evidence of an ‘‘optimum tree density’’ with respect to mean annual rainfall in our study area, we established a tree-density gradient of 20, 40, and 60 trees ha -1 , coded D20, D40, and D60, respectively. Trees in D40 plots had higher speciﬁc leaf area (SLA) values and the highest water content. Both D20 and D60 trees had leaves with higher dry matter content (LDMC). The trade-off between SLA and LDMC was very strong and placed D40 trees as the least stressed, in terms of leaf anatomy. We also found differences in mean carbon isotope discrimination (D), between different density plots, as big as 1.25%. Again, D40 trees discriminated more against 13 C than the trees from D20 and D60 plots, which suggests a less conservative water use strategy, possibly deriving from greater water availability. The lower water retention in the D20 areas and the increased competition for water resources in D60 plots placed trees, in both areas, in a more stressful situation, regarding water availability. The D40 areas thus seemed to represent a more favourable environment for Q. suber in our montado. Therefore, the areas with 40 trees ha -1 suggest the existence of an optimum tree density with respect to annual rainfall in our site, and may represent a compromise between an increased retention of water resources and intraspeciﬁc competition.
Keywords: carbon isotope discrimination; evergreen oak; montado; Specific leaf area; stand density